Clinical Applications of Cyberpsychology and Virtual Reality for Mental Disorders - Bouchard, Stéphane (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The fields of cyberpsychology, e-health and virtual reality have evolved during the last 20 years and this Special Issue is devoted to recent developments in the understanding and treatment of psychological and mental disorders. Researchers have studied how mental health can be delivered online decades before the COVID-19 pandemic. This knowledge suddenly became invaluable when professionals had to find alternative ways to provide psychotherapy and other services. Reprints from articles about telepsychology include results from randomized control trials and studies trying to isolate and understand factors involved in treatment processes and acceptability. It is followed by a literature review on virtual reality applications on mental health. The authors then address how the human body is experienced and how it impacts body image and pain. The Special Issue concludes with innovative work on how virtual reality could be used for depression.